(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This article lists the incidence of iron deficiency anemia, clinical signs, preventive measures, in which iron deficiency anemia is now 12% among women in developed countries. This in itself is known that if in developed countries this figure is as follows, then in other countries this number is much higher. According to the latest data from the World Health Organization, currently 1.8 billion people worldwide suffer from iron deficiency anemia. The prevalence of iron deficiency anemia is not the same in all countries, which in most cases will depend on the social and economic conditions of the states.